Preparation method of multi-dimensional polymer nanostructure with controllable morphology

Through interface self-assembly and external stimulation induction of block polymers, the problem of difficulty in controlling morphology of nanostructures in the prior art is solved, and the morphology, size and function regulation of multi-dimensional polymer nanostructures is realized, and it is suitable for a variety of applications field.

CN119286006AActive Publication Date: 2025-01-10TECHNICAL INST OF PHYSICS & CHEMISTRY - CHINESE ACAD OF SCI
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411428711.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-14
Publication Date
2025-01-10
Estimated Expiration
2044-10-14

AI Technical Summary

Technical Problem

The prior art has problems such as difficulty in morphology control, limited material selection, complex preparation process and difficulty in mass production when preparing nanostructures, especially in template method, etching method and chemical deposition method.

Method used

Using block polymers as raw materials, a multi-dimensional polymer nanostructure is formed on the growth substrate through solvent volatility and self-assembly processes. The interface self-assembly of hydrophobic chain segments and hydrophilic chain segments is used to combine external stimulation induction to achieve controllable morphology. nanostructure preparation.

Benefits of technology

The morphology, size and function of multidimensional polymer nanostructures has been controlled, with the advantages of controllable surface morphology, adjustable chemical properties, and easy to prepare on a large scale. It is suitable for liquid biopsy, tumor diagnosis, drug release and catalytic nanostructures and other fields.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119286006A_ABST
    Figure CN119286006A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of nanostructure preparation, in particular to a preparation method of a morphology-controllable multi-dimensional polymer nanostructure. Comprising the following steps: 1, dissolving a block polymer in an organic solvent, and adding a functional unit for assisting special structure preparation and functions into the organic solvent to prepare a growth solution; 2, dissolving a certain amount of a surfactant in water to serve as a growth environment; 3, putting an area-adjustable growth substrate into the growth environment in the step 2, and applying the growth solution in the step 1 to the growth substrate; and 4, applying external stimulation induction to the growth solution in the step 3, and enabling the growth solution to grow into a nano structure on the growth substrate through solvent volatilization and self-assembly processes. The preparation method is simple in process, easy for large-scale preparation, suitable for various substrate materials, high in controllability and capable of preparing the multi-dimensional polymer nanostructures which are different in structure length, different in structure size, uniform in structure and capable of achieving various functions through simple regulation and control.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of nanostructure preparation, and in particular to a method for preparing a multi-dimensional polymer nanostructure with controllable morphology. Background Art

[0002] In recent decades, nanostructures have attracted widespread research interest due to their large specific surface area, unique surface nanostructures, and a wide range of material choices. They have been widely used in the fields of battery nanostructures, catalyst loading, biomolecule delivery, cell regulation, and cell capture.

[0003] At present, the main methods for preparing nanostructures are: template method, chemical deposition method, etching method, self-assembly method, etc. When preparing nanostructures using the template method, although the surface morphology of the nanostructure is regular and controllable, the preparation and removal process of the nanotemplate is relatively complicated, and there are disadvantages such as a long preparation process and difficulty in large-scale preparation. When preparing nanostructures using the etching method, nanostructures with controllable morphology spacing can be prepared, but because ion gas or corrosive acid is used for etching, the preparation conditions are relatively harsh and the materials that can be selected are relatively limited. When preparing nanostructures using the chemical deposition method, although the process flow is simplified to a certain extent and nanostructures with regular and controllable morphology can be prepared, the materials used in the chemical deposition method are mostly inorganic materials, and the selectivity of the substrate is relatively limited.

[0004] Block copolymers can form regular and ordered structures through microphase separation, based on which nanostructures can be prepared by polymer self-assembly methods, thereby producing membranes with uniform pore size and pore size distribution. Specifically, the formation of different microphase separation structures of block copolymers can be controlled by solvent vapor treatment, external electric field induction, non-solvent induced phase separation, etc., among which solvent vapor treatment and external electric field induction are still in the laboratory preparation stage and difficult to mass produce. However, in the existing recorded treatment methods for non-solvent induced phase separation, block copolymers mostly need to be self-assembled on a support layer of a specific structure and then composited with the support layer to obtain a surface burr structure nanostructure, and the use of base materials has limitations.

[0005] Therefore, the present application proposes a method for preparing a multi-dimensional polymer nanostructure with controllable morphology. Summary of the invention

[0006] In order to make up for the deficiencies of the prior art and solve the technical problems existing in the background technology, the present invention proposes a method for preparing a multi-dimensional polymer nanostructure with controllable morphology.

[0007] The present invention is achieved through the following technical solutions: A method for preparing a multidimensional polymer nanostructure with controllable morphology comprises the following steps: Step 1: dissolving the block polymer in an organic solvent and adding functional units that assist in the preparation of special structures and functions to prepare a growth solution; Step 2: dissolving a certain amount of surfactant in water as a growth environment; Step 3: placing the growth substrate with adjustable area into the growth environment of step 2, and applying the growth liquid of step 1 thereto; Step 4: applying external stimulation to the step 3, and after the solvent volatilization and self-assembly process, the growth liquid grows into a nanostructure on the growth substrate.

[0008] The dimension of the nanostructure mainly describes the dimension of the growth substrate, including but not limited to one or more of a one-dimensional tube, a one-dimensional wire, a two-dimensional plane, a three-dimensional inner sphere, and a three-dimensional grid.

[0009] Preferably, the block polymer includes a polymer of two segments, three segments or more than three blocks or a multi-arm block polymer or a hyperbranched polymer, and the block polymer has a hydrophobic segment and a hydrophilic segment, and the weight ratio of the hydrophobic segment to the hydrophilic segment is (0.5-100):1.

[0010] The molecular weight of the hydrophobic segment is 10KDa-200KDa, and the molecular weight of the hydrophilic segment is 1KDa-100KDa.

[0011] Only by using the above-mentioned hydrophilic and hydrophobic segments can self-assembly on the interface be initiated, thereby preparing the nanostructure in one step.

[0012] On a theoretical level, hydrophilic polymers tend to accumulate at the oil-water interface. Then, under the combined action of specific external stimuli and the elastic force of the hydrophobic segments, the interface is controlled to deform outward to gain more space, thereby completing the preparation of the nanostructure in one step.

[0013] In this process, the length, ratio, type and external stimulation of the hydrophilic and hydrophobic ends will affect the growth rate and structural appearance of the nanostructure.

[0014] In general, the smaller the rigidity of the hydrophobic segment, the richer the structure; the shorter the length of the hydrophobic segment, the richer the structure; the more hydrophilic the hydrophilic segment, the richer the structure; the longer the hydrophilic segment, the richer the structure.

[0015] Preferably, the hydrophobic segment comprises one or more of polystyrene, polymethyl methacrylate, polylactic acid, polylactide, polylactic acid / glycolic acid copolymer, polydimethylsiloxane, and polyisobutylene.

[0016] Preferably, the hydrophilic segment comprises one or more of poly-4-vinylpyridine, polyacrylic acid, polyethylene glycol, poly(polyethylene glycol methyl ether methacrylate), and poly-N,N-dimethylacrylamide.

[0017] Preferably, the organic solvent comprises one or more of ethyl acetate, dimethyl carbonate, ethylene glycol dimethyl ether, dioxane, benzene, toluene, xylene, dichloromethane, chloroform, 1,2-dichloroethane, trichloroethane, carbon tetrachloride, tetrahydrofuran, N,N-dimethylformamide, and acetone; and the concentration of the growth solution in step 1 is 0.1-500 mg / ml.

[0018] Preferably, the functional unit includes one or more of ferroferric oxide nanoparticles, gold nanoparticles, silver nanoparticles, graphene nanosheets, quantum dots, doxorubicin, paclitaxel, quaternary ammonium salts, and gene transfection molecules.

[0019] For example: ferroferric oxide nanoparticles affect their structure, gold generates heat, silver is antibacterial, graphene generates heat, and doxorubicin is anti-cancer.

[0020] Preferably, the surfactant comprises one or more of sodium dodecyl sulfate, hexadecyltrimethylammonium bromide, and polyvinyl alcohol; and the concentration of the surfactant in the growth environment in step 2 is 0-100 mg / ml.

[0021] Preferably, the growth substrate comprises one or more of a hollow tube, a solid wire, a flat sheet, a rough sheet, a water-in-oil emulsion, and a hollow grid; The surface of the growth substrate has a specific structure or is made of multiple materials; the specific structure includes a topological micron column, a cone array, a microfluidic channel or a porous grid; The various materials include glass, iron, copper, aluminum oxide, polydimethylsiloxane, polyethylene, polyimide or cross-linked polyurethane.

[0022] Preferably, the external stimulation includes physical methods such as heat, magnetism, electricity, and light, and the duration of the external stimulation is 0-24 hours; Wherein, the thermophysical method includes thermal stimulation, which is used to adjust the growth environment temperature between 0-80°C; The magnetic physics method includes applying a magnetic field, and the magnetic field includes a parallel magnetic field and a uniform magnetic field, and the magnetic field intensity ranges from 0 to 50 mT, and the uniform magnetic field frequency ranges from 0 to 200 Hz; The electrophysical method includes electrical stimulation, and the electrical stimulation includes applying a voltage of a certain intensity, and the electrical stimulation power range is 0-36W; The photophysical method includes light stimulation, and the light stimulation includes applying light waves of a certain wavelength band, and the wavelength of the light waves is 450nm, 532nm, 808nm, and 1064nm.

[0023] Preferably, the morphology of the nanostructure includes one or more combinations of a nano-burr structure, a nano-dot structure, a nano-wire structure, a nano-hole structure, and a nano-mesh structure.

[0024] The beneficial effects of the present invention are: 1. The present invention uses block polymer as raw material, dissolves it in an organic solvent, then slowly adds the block copolymer solution onto the hydrophobic surface of the target substrate of deionized water, and injects the surfactant aqueous solution, and obtains a multi-dimensional polymer nanostructure with controllable morphology through the self-assembly process of the block polymer during solvent evaporation.

[0025] 2. The multidimensional polymer nanostructure prepared by the present invention can control the morphology, size and function of its multidimensional surface. By adjusting the type of segment polymer, the number of blocks, the molecular weight of the block polymer, the concentration, the reaction temperature and the functional unit, multidimensional polymer nanostructures with different morphologies, different surface properties and different functions can be achieved.

[0026] 3. The present invention has the advantages of controllable surface morphology, adjustable chemical properties, easy large-scale preparation, a variety of substrates can be selected, and broad prospects for industrial application. The prepared multi-dimensional polymer nanostructure with controllable morphology has great application prospects in chemical, biological and industrial fields such as liquid biopsy, tumor diagnosis, drug release, catalytic nanostructures, and oil-water separation. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 This is a scanning electron microscope photograph of the multidimensional polymer nanostructure prepared in Example 1 of the present invention; Figure 2 This is a scanning electron microscope photograph of the multidimensional polymer nanostructure prepared in Example 2 of the present invention; Figure 3 This is a scanning electron microscope photograph of the multidimensional polymer nanostructure prepared in Example 3 of the present invention; Figure 4 This is a scanning electron microscope photograph of the multidimensional polymer nanostructure prepared in Example 4 of the present invention; Figure 5 This is a scanning electron microscope photograph of the multidimensional polymer nanostructure prepared in Example 6 of the present invention; Figure 6 This is a scanning electron microscope photograph of the multidimensional polymer nanostructure prepared in Example 7 of the present invention; Figure 7 This is a scanning electron microscope photograph of the multidimensional polymer nanostructure prepared in Example 9 of the present invention; Figure 8 The multi-dimensional polymer nanostructure phase diagram obtained by changing the ratio of hydrophilic and hydrophobic polymers in the present invention; Fig. 9 This is a scanning electron microscope photograph of the multidimensional polymer nanostructure prepared in Example 10 of the present invention; Fig.10This is a scanning electron microscope photograph of the multidimensional polymer nanostructure prepared in Example 11 of the present invention; Fig.11 This is a scanning electron microscope photograph of the multidimensional polymer nanostructure prepared in Example 12 of the present invention; Fig.12 This is a scanning electron microscope photograph of the multidimensional polymer nanostructure prepared in Example 14 of the present invention; Fig.13 This is a scanning electron microscope photograph of the multidimensional polymer nanostructure prepared in Example 15 of the present invention; Fig.14 A graph showing the relationship between the number of burrs and the segment ratio in Examples 1-3 of the present invention; Fig.15 This is a graph showing the relationship between the pore size and the segment ratio in Examples 4-6 of the present invention; Fig.16 This is a diagram showing the relationship between the burr thickness and the segment ratio in Examples 1-3 of the present invention. DETAILED DESCRIPTION

[0028] The present invention will be further described below in conjunction with specific examples. It should be understood that these examples are only used to illustrate the present invention and are not intended to limit the scope of the present invention. The experimental methods in the following examples without specifying specific conditions are usually carried out under conventional conditions or under conditions recommended by the manufacturer.

[0029] Unless otherwise defined, all professional and scientific terms used herein have the same meanings as those familiar to those skilled in the art. The reagents or raw materials used in the present invention can be purchased through conventional channels. Unless otherwise specified, the reagents or raw materials used in the present invention are used in a conventional manner in the art or in accordance with the product instructions. In addition, any method and material similar to or equivalent to the described content can be applied to the method of the present invention. The present invention is further described according to the accompanying drawings and specific embodiments of the present invention, and the preferred implementation methods and materials described in the present invention are only for demonstration purposes.

[0030] Example 1, adjusting the polymer ratio to control the nanostructure: Preparation of growth solution: The diblock polymer polystyrene-b-polyetherimide PS30K-b-PEI4K was dissolved in ethyl acetate at a concentration of 10% w / v (mass / volume). During the dissolution process, it was placed on a shaker at 100 r / min for 60 min to ensure sufficient shaking. The subscripts of the polymer PS30K-b-PEI4K indicate the molecular weights of different segments in the polymer, i.e., polystyrene-polyetherimide block copolymer, polystyrene molecular weight 30 KDa, polyetherimide molecular weight 4 KDa, and this expression is used in the subsequent embodiments. Fe with an average particle size of 50 nm modified with surface oleic acid was added to the dissolved ethyl acetate solution at a concentration of 0.1% w / v.3 O 4 The nanoparticles were ultrasonically shaken for 10 min to fully disperse, thereby completing the configuration of the growth solution; Selecting a growth substrate: Selecting a hydrophobically modified silicon wafer substrate. In this embodiment, perfluorodecyltrimethoxysilane is selected for gas phase hydrophobic modification. After modification, the contact angle is about 120°. Growth environment: Sodium dodecyl sulfate was dissolved in deionized water at a concentration of 2% w / v, at 40°C, 400 r / min, and stirred for half an hour to achieve full dissolution; Select external stimulation: select light intensity of 5mW / cm 2 The 808nm near-infrared light source was used for external stimulation, and the illumination area was 1cm 2 , illumination distance is 3cm, illumination time is 2h; Growth steps: Place the growth substrate in the growth environment, use a dropper to apply 200 μL of growth solution to the growth substrate, fix the near-infrared light source at a height of 3 cm from the center of the growth substrate, start illumination, and after the growth is completed, take it out of the solution, wash it, and observe the growth results; Growth results: as attached Figure 1 As shown, SEM characterization showed that the multidimensional polymer nanostructure prepared by this method showed abundant nanoscale burr structures on the two-dimensional silicon substrate plane. The nanoburr structure had a diameter of about 100 nm and a length of about 500 nm. The structure size was uniform and there were no obvious defects.

[0031] Example 2, adjusting the polymer ratio to control the nanostructure: Prepare the growth solution: dissolve the diblock polymer polystyrene-b-polyetherimide PS50K-b-PEI4K in ethyl acetate at a concentration of 10% w / v (mass / volume). Place the solution in a shaker at 100 r / min for 60 min to ensure adequate shaking. Add 0.1% w / v of Fe with an average particle size of 50 nm modified with surface oleic acid to the dissolved ethyl acetate solution. 3 O 4 The nanoparticles were ultrasonically shaken for 10 min to fully disperse, thereby completing the configuration of the growth solution; Selecting a growth substrate: Selecting a hydrophobically modified silicon wafer substrate. In this embodiment, perfluorodecyltrimethoxysilane is selected for gas phase hydrophobic modification. After modification, the contact angle is about 120°. Configure the growth environment: dissolve sodium dodecyl sulfate in deionized water at a concentration of 2% w / v, at 40°C, 400 r / min, and stir for half an hour to achieve full dissolution; Select external stimulation: select light intensity of 5mW / cm 2 The 808nm near-infrared light source was used for external stimulation, and the illumination area was 1cm2 , illumination distance is 3cm, illumination time is 2h; Growth steps: Place the growth substrate in the growth environment, use a dropper to apply 200 μL of growth solution to the growth substrate, fix the near-infrared light source at a height of 3 cm from the center of the growth substrate, start illumination, and after the growth is completed, take it out of the solution, wash it, and observe the growth results; Growth results: as attached Figure 2 As shown, through SEM characterization, the multidimensional polymer nanostructure prepared by this method presents abundant nanoscale burr structure on the two-dimensional silicon substrate plane. The diameter of the nanoburr structure is about 100nm and the length is about 300nm. Compared with Example 1, the burr length and density are reduced, the structure size is uniform, and there are no obvious defects.

[0032] Example 3, adjusting the polymer ratio to control the nanostructure: Prepare the growth solution: dissolve the diblock polymer polystyrene-b-polyetherimide PS70K-b-PEI4K in ethyl acetate at a concentration of 10% w / v (mass / volume). Place the solution in a shaker at 100 r / min for 60 min to ensure adequate shaking. Add 0.1% w / v of Fe with an average particle size of 50 nm modified with surface oleic acid to the dissolved ethyl acetate solution. 3 O 4 Nanoparticles were ultrasonically vibrated for 10 minutes to fully disperse, thereby completing the configuration of the growth solution. Selecting a growth substrate: Selecting a hydrophobically modified silicon wafer substrate. In this embodiment, perfluorodecyltrimethoxysilane is selected for gas phase hydrophobic modification. After modification, the contact angle is about 120°. Growth environment: Sodium dodecyl sulfate was dissolved in deionized water at a concentration of 2% w / v, at 40°C, 400 r / min, and stirred for half an hour to achieve full dissolution; Select external stimulus: select light intensity of 5mW / cm 2 The 808nm near-infrared light source was used for external stimulation, and the illumination area was 1 cm 2 The illumination distance is 3 cm and the illumination time is 2 h; Growth steps: Place the growth substrate in the growth environment, use a dropper to apply 200 μL of growth solution to the growth substrate, fix the near-infrared light source at a height of 3 cm from the center of the growth substrate, start illumination, and after the growth is completed, take it out of the solution, wash it, and observe the growth results; Growth results: as attached Figure 3As shown, through SEM characterization, the multidimensional polymer nanostructure prepared by the method presents abundant nanoscale burr structure on the two-dimensional silicon substrate plane. The diameter of the nano-burr structure is about 100nm and the length is about 100nm. Compared with Example 1, the burr length is reduced, and the structure is transformed from a burr structure to a point structure. The structure size is uniform and there are no obvious defects.

[0033] Examples 1-3 reflect that the structure is regulated by adjusting the ratio of hydrophilic and hydrophobic blocks in the polymer. As the hydrophobic ratio increases, the growth of the structure becomes difficult, and the length and density of the structure both decrease.

[0034] Example 4, adjusting the polymer ratio to control the nanostructure: Prepare the growth solution: dissolve the diblock polymer polystyrene-b-polyetherimide PS30K-b-PEI10K in ethyl acetate at a concentration of 10% w / v (mass / volume). Place the solution on a shaker at 100 r / min for 60 min to ensure adequate shaking. Add 0.1% w / v of Fe with an average particle size of 50 nm modified with surface oleic acid to the dissolved ethyl acetate solution. 3 O 4 The nanoparticles were ultrasonically vibrated for 10 min to fully disperse, thereby completing the configuration of the growth solution; Selecting a growth substrate: Selecting a hydrophobically modified silicon wafer substrate. In this embodiment, perfluorodecyltrimethoxysilane is selected for gas phase hydrophobic modification. After modification, the contact angle is about 120°. Configure the growth environment: dissolve sodium dodecyl sulfate in deionized water at a concentration of 2% w / v, at 40°C, 400 r / min, and stir for half an hour to achieve full dissolution; Select external stimulus: select light intensity of 5mW / cm 2 The 808nm near-infrared light source was used for external stimulation, and the illumination area was 1 cm 2 , illumination distance is 3cm, illumination time is 2h; Growth steps: Place the growth substrate in the growth environment, use a dropper to apply 200 μL of growth solution to the growth substrate, fix the near-infrared light source at a height of 3 cm from the center of the growth substrate, start illumination, and after the growth is completed, take it out of the solution, wash it, and observe the growth results; Growth results: as attached Figure 4As shown, after SEM characterization, the multi-dimensional polymer nanostructure prepared by this method presents a rich nanoscale pore structure on the two-dimensional silicon substrate plane, and the structure changes from a burr structure to a pore structure, but there is still a similar line-like structure on the surface of the pore wall. It is speculated that the burr structure is in the transition from a pore structure to a burr structure, and the residual burr structure has a uniform structure size and no obvious defects. Examples 1 and 4 reflect the regulation of the structure by adjusting the ratio of hydrophilic and hydrophobic blocks in the polymer. As the ratio of hydrophilic segments increases, the structure is easier to grow and the structure changes to a porous state.

[0035] Example 5, adjusting the polymer ratio to control the nanostructure: Preparation of growth solution: Dissolve the diblock polymer polystyrene-b-polyetherimide PS50K-b-PEI10K in ethyl acetate at a concentration of 10% w / v (mass / volume). During the dissolution process, place it on a shaker at 100 r / min for 60 min to ensure sufficient shaking. Add 0.1% w / v of Fe with an average particle size of 50 nm modified with surface oleic acid to the dissolved ethyl acetate solution. 3 O 4 The nanoparticles were ultrasonically shaken for 10 min to fully disperse, thereby completing the configuration of the growth solution; Selecting a growth substrate: Selecting a hydrophobically modified silicon wafer substrate. In this embodiment, perfluorodecyltrimethoxysilane is selected for gas phase hydrophobic modification. After modification, the contact angle is about 120°. Growth environment: Dissolve sodium dodecyl sulfate in deionized water at a concentration of 2% w / v. Dissolution process at 40°C, 400r / min, stirring for half an hour to achieve full dissolution; Select external stimulus: select light intensity of 5mW / cm 2 The 808nm near-infrared light source was used for external stimulation, and the illumination area was 1 cm 2 , illumination distance is 3cm, illumination time is 2h; Growth steps: Place the growth substrate in the growth environment, use a dropper to apply 200 μL of growth solution to the growth substrate, fix the near-infrared light source at a height of 3 cm from the center of the growth substrate, start illumination, and after the growth is completed, take it out of the solution, wash it, and observe the growth results; Growth results: SEM characterization showed that the multidimensional polymer nanostructure prepared by this method showed abundant nanoscale pore structure on the two-dimensional silicon substrate plane. Compared with Example 1, the structure was completely transformed into a pore structure with uniform structure size and no obvious defects.

[0036] Example 6, adjusting the polymer ratio to control the nanostructure: Prepare the growth solution: dissolve the diblock polymer polystyrene-b-polyetherimide PS70K-b-PEI10K in ethyl acetate at a concentration of 10% w / v (mass / volume). Place the solution on a shaker at 100 r / min for 60 min to ensure adequate shaking. Add 0.1% w / v of Fe with an average particle size of 50 nm modified with surface oleic acid to the dissolved ethyl acetate solution. 3 O 4 The nanoparticles were ultrasonically vibrated for 10 min to fully disperse, thereby completing the configuration of the growth solution; Selecting a growth substrate: Selecting a hydrophobically modified silicon wafer substrate. In this embodiment, perfluorodecyltrimethoxysilane is selected for gas phase hydrophobic modification. After modification, the contact angle is about 120°. Growth environment: Sodium dodecyl sulfate was dissolved in deionized water at a concentration of 2% w / v, at 40°C, 400 r / min, and stirred for half an hour to achieve full dissolution; Select external stimulus: select light intensity of 5mW / cm 2 The 808nm near-infrared light source was used for external stimulation, and the illumination area was 1 cm 2 , illumination distance is 3cm, illumination time is 2h; Growth steps: Place the growth substrate in the growth environment, use a dropper to apply 200 μL of growth solution to the growth substrate, fix the near-infrared light source at a height of 3 cm from the center of the growth substrate, start illumination, and after the growth is completed, take it out of the solution, wash it, and observe the growth results; Growth results: as attached Figure 5 As shown, through SEM characterization, the multidimensional polymer nanostructure prepared by this method presents abundant nanoscale pore structure on the two-dimensional silicon substrate plane. Compared with Example 5, the structure is completely transformed into a pore structure with uniform structure size and no obvious defects.

[0037] Examples 4-6 show that the structure is regulated by adjusting the ratio of hydrophilic and hydrophobic segments in the polymer. As the hydrophobic ratio increases, the growth of the structure becomes difficult, and the structure changes from porous to a composite structure of porous and burred. Comparison of Examples 1-3 and 4-6 shows that the structure is regulated by adjusting the ratio of hydrophilic segments in the polymer. As the hydrophilic ratio increases, the growth of the structure becomes easy, and the structure changes from burred to porous.

[0038] Example 7, changing the polymer type: Preparation of growth solution: dissolve the triblock polymer polyglycolide-co-lactide-b-polyethylene glycol-b-polyglycolide-co-lactide PLGA50K-b-PEO4K-b-PLGA50K in dichloromethane at a concentration of 10% w / v (mass / volume). During the dissolution process, place it on a shaker at 100 r / min for 60 min to ensure sufficient shaking, thereby completing the preparation of the growth solution; Selecting a growth substrate: Selecting a hydrophobically modified silicon wafer substrate. In this embodiment, perfluorodecyltrimethoxysilane is selected for gas phase hydrophobic modification. After modification, the contact angle is about 120°. Growth environment: Sodium dodecyl sulfate was dissolved in deionized water at a concentration of 2% w / v, at 40°C, 400 r / min, and stirred for half an hour to achieve full dissolution; Select external stimulation: select a water bath heated to 50°C, the water bath height is higher than the growth environment height, and start the growth step after keeping warm for 1 hour, and the growth time is 4 hours; Growth steps: Place the growth substrate in the growth environment, use a dropper to apply 200 μL of growth solution to the growth substrate, let it grow for 4 hours, take it out of the solution after the growth is completed, wash it, and observe the growth results; Growth results: as attached Figure 6 As shown, SEM characterization shows that the multidimensional polymer nanostructure prepared by this method presents abundant nanoscale burr structures on the two-dimensional silicon substrate plane, with uniform structure size and no obvious defects. Compared with the nanostructure in Example 1, the burr structure in this embodiment is longer, reaching about 1 μm.

[0039] Comparison of Example 1 and Example 7 shows that similar nanostructures can be obtained by changing the appropriate number of block polymer segments, the chemical composition of the hydrophilic and hydrophobic segments, and the ratio of segment lengths; that is, when there is an oil-water interface, the hydrophilic and hydrophobic block polymers of a specific composition can form a controllable nanostructure spontaneously or under simple external stimulation.

[0040] Example 8, changing the growth environment: Preparation of growth solution: dissolve the triblock polymer polyglycolide-co-lactide-b-polyethylene glycol-b-polyglycolide-co-lactide PLGA50K-b-PEO4K-b-PLGA50K in dichloromethane at a concentration of 10% w / v (mass / volume). During the dissolution process, place it on a shaker at 100 r / min for 60 min to ensure sufficient shaking, thereby completing the preparation of the growth solution; Selecting a growth substrate: Selecting a hydrophobically modified silicon wafer substrate. In this embodiment, perfluorodecyltrimethoxysilane is selected for gas phase hydrophobic modification. After modification, the contact angle is about 120°. Growth environment: Dissolve polyvinyl alcohol in deionized water at a concentration of 2% w / v, at 80°C, 400 r / min, and stir for half an hour to achieve full dissolution; Select external stimulation: select a water bath heated to 80°C, the water bath height is higher than the growth environment height, keep warm for 1 hour before starting the growth step, and the growth time is 4 hours; Growth steps: Place the growth substrate in the growth environment, use a dropper to apply 200 μL of growth solution to the growth substrate, let it grow for 4 hours, take it out of the solution after the growth is completed, wash it, and observe the growth results; Growth results: SEM characterization showed that the multidimensional polymer nanostructure prepared by this method showed abundant nanoscale burr structures on the two-dimensional silicon substrate plane. Compared with Example 7, the richness of the structure was reduced, and the nanowires were transformed into nanodots, indicating that the increase in the preparation environment temperature limited the growth of the nanostructure, and the structure size was uniform without obvious defects.

[0041] Example 9, changing the polymer ratio: Preparation of growth solution: dissolve the triblock polymer polyglycolide-co-lactide-b-polyethylene glycol-b-polyglycolide-co-lactide PLGA70K-b-PEO4K-b-PLGA70K in dichloromethane at a concentration of 20% w / v (mass / volume). During the dissolution process, place it on a shaker at 100 r / min for 60 minutes to ensure sufficient shaking, thereby completing the preparation of the growth solution; Selecting a growth substrate: Selecting a hydrophobically modified silicon wafer substrate. In this embodiment, perfluorodecyltrimethoxysilane is selected for gas phase hydrophobic modification. After modification, the contact angle is about 120°. Growth environment: Dissolve polyvinyl alcohol in deionized water at a concentration of 2% w / v, at 80°C, 400 r / min, and stir for half an hour to achieve full dissolution; Select external stimulation: select a water bath heated to 50°C, the water bath height is higher than the growth environment height, and start the growth step after keeping warm for 1 hour, and the growth time is 4 hours; Growth steps: Place the growth substrate in the growth environment, use a dropper to apply 200 μL of growth solution to the growth substrate, let it grow for 4 hours, take it out of the solution after the growth is completed, wash it, and observe the growth results; Growth results: as attached Figure 7 As shown, through SEM characterization, the multidimensional polymer nanostructure prepared by this method presents a rich nanoscale dot structure on the two-dimensional silicon substrate plane. Compared with Example 7, the structural richness is reduced, and the nanowires are transformed into nanodots, indicating that increasing the proportion of hydrophobic segments limits the growth of the nanostructure, and the structure size is uniform without obvious defects.

[0042] Example 10, changing the growth substrate: Preparation of growth solution: dissolve the triblock polymer polyglycolide-co-lactide-b-polyethylene glycol-b-polyglycolide-co-lactide PLGA50K-b-PEO4K-b-PLGA50K in dichloromethane at a concentration of 20% w / v (mass / volume). During the dissolution process, place it on a shaker at 100 r / min for 60 min to ensure sufficient shaking, thereby completing the preparation of the growth solution; Selecting a growth substrate: Selecting a rough glass substrate that has been hydrophobically modified. In this embodiment, perfluorodecyltrimethoxysilane is selected for gas phase hydrophobic modification. After modification, the contact angle is about 150°. Growth environment: Dissolve polyvinyl alcohol in deionized water at a concentration of 2% w / v; dissolve at 80°C, 400r / min, and stir for half an hour to achieve full dissolution; Select external stimulation: select a water bath heated to 50°C, the water bath height is higher than the growth environment height, and start the growth step after keeping warm for 1 hour, and the growth time is 4 hours; Growth steps: Place the growth substrate in the growth environment, use a dropper to apply 200 μL of growth solution to the growth substrate, let it grow for 4 hours, take it out of the solution after the growth is completed, wash it, and observe the growth results; Growth results: as attached Fig. 9 As shown, SEM characterization shows that the multidimensional polymer nanostructure prepared by this method presents abundant nanoscale burr structures on the rough glass substrate, which are combined into a micro-nano conformal structure, with both micron-scale undulating structures and nanoscale burr structures, indicating that this method can obtain a variety of desired structures by changing the preparation substrate.

[0043] Example 11, changing the growth substrate to a water-in-oil emulsion: Preparation of growth solution: dissolve the triblock polymer polyglycolide-co-lactide-b-polyethylene glycol-b-polyglycolide-co-lactide PLGA50K-b-PEO4K-b-PLGA50K in dichloromethane at a concentration of 20% w / v (mass / volume). During the dissolution process, place it on a shaker at 100 r / min for 60 min to ensure sufficient shaking, thereby completing the preparation of the growth solution; Selecting a growth substrate: Selecting a glass substrate that has been hydrophobically modified. In this embodiment, perfluorodecyltrimethoxysilane is selected for gas phase hydrophobic modification. After modification, the contact angle is about 120°. Growth environment: Dissolve sodium dodecyl sulfate in deionized water at a concentration of 2% w / v. Dissolution process 80℃, 400r / min, stirring for half an hour to achieve full dissolution; Select external stimulation: select ultrasonic equipment, press 100% ultrasonic power, ultrasonicate for 5 seconds per minute, maintain the water bath temperature at 25°C, start ultrasonication after adding the growth solution, and the growth time is 2 hours; Growth steps: Place the growth substrate in the growth environment, use a dropper to apply 200 μL of growth solution to the growth substrate, let it grow for 2 hours, take it out of the solution after the growth is completed, wash it, and observe the growth results; Growth results: as attached Fig.10 As shown, after SEM characterization, the multidimensional polymer nanostructure prepared by the method presents a burr structure that grows inward in the polymer body phase. Compared with Example 7, the structure is completely similar, the structure size is uniform, and there is no obvious defect, but the growth direction is different, indicating that the method does not fix the formation mode of the oil-water interface. Regardless of the form of water-in-oil, water-oil plane or oil-in-water, as long as there is an oil-water interface, the method can grow the nanostructure.

[0044] Example 12, changing the growth substrate to a one-dimensional tube: Preparation of growth solution: dissolve the diblock polymer polymethyl methacrylate-b-poly-4-vinylpyridine PMMA30K-b-P4VP8K in dichloromethane at a concentration of 5% w / v (mass / volume). During the dissolution process, place it on a shaker at 100 r / min for 60 min to ensure sufficient shaking, thereby preparing the growth solution; Selecting a growth substrate: Selecting a hydrophobic modified capillary. In this embodiment, silica nanoparticles modified with perfluorodecyltrimethoxysilane are selected for liquid phase modification. In simple terms, a commercially available super-hydrophobic powder dispersion is used as the modification liquid. The capillary treated with oxygen plasma is immersed in the modification liquid and then taken out and dried. Growth environment: Sodium dodecyl sulfate was dissolved in deionized water at a concentration of 2% w / v, at 80°C, 400 r / min, and stirred for half an hour to achieve full dissolution; Select external stimulation: select ultrasonic equipment, press 100% ultrasonic power, ultrasonicate for 5 seconds per minute, maintain the water bath temperature at 25°C, start ultrasonication after adding the growth solution, and the growth time is 2 hours; Growth steps: Place the growth substrate in the growth environment, use a dropper to apply 200 μL of growth solution to the growth substrate, let it grow for 2 hours, take it out of the solution after the growth is completed, wash it, and observe the growth results; Growth results: as attached Fig.11 As shown, through SEM characterization, the multidimensional polymer nanostructure prepared by this method presents a burr structure growing into the tube in a one-dimensional capillary. Compared with Example 7, the structure is completely similar, the structure size is uniform, and there is no obvious defect.

[0045] Example 13, changing the growth substrate to a cross-linked PDMS substrate coated with two-dimensional copper interdigital electrodes: Prepare the growth solution: Dissolve the polymer polydimethylsiloxane-b-polyethylene glycol PDMS30K-b-PEO8K in chloroform at a concentration of 10% w / v (mass / volume). During the dissolution process, place it on a shaker at 100 r / min for 60 minutes to ensure sufficient shaking, thereby preparing the growth solution.

[0046] Selecting a growth substrate: selecting a cross-linked PDMS substrate coated with a two-dimensional copper interdigital electrode after hydrophobic modification. In this embodiment, the two-dimensional interdigital electrode is encapsulated in an asymmetrically modified PDMS, and the asymmetrical modification of the PDMS is performed by using a mask covering method and selecting perfluorodecyltrimethoxysilane vapor phase modification; Growth environment: Sodium dodecyl sulfate was dissolved in deionized water at a concentration of 2% w / v, at 80°C, 400 r / min, and stirred for half an hour to achieve full dissolution; Select external stimulation: energize the interdigital electrodes at 15V / 2A for 30 minutes. Growth steps: Place the growth substrate in the growth environment, use a dropper to apply 500μL of growth solution to the growth substrate, and turn on the power to grow for 30 minutes. After the growth is completed, take it out of the solution, clean it, and observe the growth results; Growth results: SEM characterization showed that the multidimensional polymer nanostructure prepared by this method showed a burr structure on the interdigitated electrode. Compared with Example 7, the structure was completely similar, the structure size was uniform, and there was no obvious defect.

[0047] Example 14, changing the growth substrate to a cross-linked PDMS microfluidic channel: Preparation of growth solution: dissolve the triblock polymer polyglycolide-co-lactide-b-polyethylene glycol-b-polyglycolide-co-lactide PLGA50K-b-PEO4K-b-PLGA50K in dichloromethane at a concentration of 20% w / v (mass / volume). During the dissolution process, place it on a shaker at 100 r / min for 60 min to ensure sufficient shaking, thereby completing the preparation of the growth solution; Selecting a growth substrate: selecting a cross-linked PDMS substrate with a microfluidic channel. In this embodiment, the PDMS is also asymmetrically modified by perfluorodecyltrimethoxysilane in the vapor phase; Growth environment: Sodium dodecyl sulfate was dissolved in deionized water at a concentration of 2% w / v, at 80°C, 400 r / min, and stirred for half an hour to achieve full dissolution; Select external stimulation: select a water bath heated to 50°C, the water bath height is higher than the growth environment height, and start the growth step after keeping warm for 1 hour, and the growth time is 4 hours; Growth steps: Place the growth substrate in the growth environment, use a dropper to apply 500 μL of growth solution to the growth substrate, let it grow for 4 hours, take it out of the solution after the growth is completed, wash it, and observe the growth results; Growth results: as attached Fig.12 As shown, through SEM characterization, the multidimensional polymer nanostructure prepared by this method presents a burr structure growing inwardly in the microfluidic channel. Compared with Example 7, the structure is completely similar, the structure size is uniform, and there is no obvious defect.

[0048] Example 15, changing the growth substrate to a cross-linked polyurethane porous grid: Preparation of growth solution: dissolve the triblock polymer polyglycolide-co-lactide-b-polyethylene glycol-b-polyglycolide-co-lactide PLGA50K-b-PEO4K-b-PLGA50K in dichloromethane at a concentration of 20% w / v (mass / volume). During the dissolution process, place it on a shaker at 100 r / min for 60 min to ensure sufficient shaking, thereby completing the preparation of the growth solution; Selecting a growth substrate: Selecting a cross-linked polyurethane with a porous grid as the substrate. In this embodiment, since the cross-linked polyurethane itself has a high hydrophobic level, hydrophobic modification is not required; Growth environment: Sodium dodecyl sulfate was dissolved in deionized water at a concentration of 2% w / v, at 80°C, 400 r / min, and stirred for half an hour to achieve full dissolution; Select external stimulation: select a water bath heated to 50°C, the water bath height is higher than the growth environment height, and start the growth step after keeping warm for 1 hour, and the growth time is 4 hours; Growth steps: Place the growth substrate in the growth environment, use a dropper to apply 1 mL of growth solution to the growth substrate, let it grow for 4 hours, take it out of the solution after the growth is completed, wash it, and observe the growth results; Growth results: as attached Fig.13 As shown, through SEM characterization, the multidimensional polymer nanostructure prepared by this method presents a burr structure growing inwardly in the microfluidic channel. Compared with Example 7, the structure is completely similar, the structure size is uniform, and there is no obvious defect.

[0049] Examples 12-15 show that the preparation method can be performed on a variety of hydrophobic substrates, thereby imparting a variety of nanostructures on the complex microstructure of the substrate itself, and the growth conditions are not harsh. Compared with traditional methods such as photolithography and etching, it has the advantages of high preparation efficiency and rich substrate selection.

[0050] Attached Figure 14-16 The statistical analysis of the effects of adjusting the ratio and length of polymer hydrophilic and hydrophobic segments on the number of burrs, burr diameter and pore diameter in Examples 1-3 and 4-6 does not limit the number and size range of the nanostructures.

[0051] Any matters not described in the present invention are applicable to the prior art.

Claims

1. A method for preparing a multidimensional polymer nanostructure with controllable morphology, characterized in that: The following steps are involved: Step 1: dissolving the block polymer in an organic solvent and adding functional units that assist in the preparation of special structures and functions to prepare a growth solution; Step 2: dissolving a certain amount of surfactant in water as a growth environment; Step 3: placing the growth substrate with adjustable area into the growth environment of step 2, and applying the growth liquid of step 1 thereto; Step 4: applying external stimulation to the step 3, and after the organic solvent volatilizes and self-assembles, the growth liquid grows into a nanostructure on the growth substrate.

2. The method for preparing a morphology-controllable multidimensional polymer nanostructure according to claim 1, characterized in that: The block polymer includes a polymer of two segments, three segments or more than three blocks or a multi-arm block polymer or a hyperbranched polymer, and the block polymer has a hydrophobic segment and a hydrophilic segment, and the weight ratio of the hydrophobic segment to the hydrophilic segment is (0.5-100):

1.

3. The method for preparing a morphology-controllable multidimensional polymer nanostructure according to claim 2, characterized in that: The hydrophobic segment includes one or more of polystyrene, polymethyl methacrylate, polylactic acid, polylactide, polylactic acid / glycolic acid copolymer, polydimethylsiloxane, and polyisobutylene.

4. The method for preparing a multi-dimensional polymer nanostructure with controllable morphology according to claim 2, characterized in that: The hydrophilic segment includes one or more of poly-4-vinylpyridine, polyacrylic acid, polyethylene glycol, poly(polyethylene glycol methyl ether methacrylate), and poly-N,N-dimethylacrylamide.

5. The method for preparing a multi-dimensional polymer nanostructure with controllable morphology according to claim 1, characterized in that: The organic solvent includes one or more of ethyl acetate, dimethyl carbonate, ethylene glycol dimethyl ether, dioxane, benzene, toluene, xylene, dichloromethane, chloroform, 1,2-dichloroethane, trichloroethane, carbon tetrachloride, tetrahydrofuran, N,N-dimethylformamide, and acetone; and the concentration of the growth solution in step 1 is 0.1-500 mg / ml.

6. The method for preparing a multi-dimensional polymer nanostructure with controllable morphology according to claim 1, characterized in that: The functional unit comprises one or more of ferroferric oxide nanoparticles, gold nanoparticles, silver nanoparticles, graphene nanosheets, quantum dots, doxorubicin, paclitaxel, quaternary ammonium salts, and gene transfection molecules.

7. The method for preparing a multi-dimensional polymer nanostructure with controllable morphology according to claim 1, characterized in that: The surfactant includes one or more of sodium dodecyl sulfate, hexadecyltrimethylammonium bromide, and polyvinyl alcohol; and the concentration of the surfactant in the growth environment in step 2 is 0-100 mg / ml.

8. The method for preparing a multi-dimensional polymer nanostructure with controllable morphology according to claim 1, characterized in that: The growth substrate comprises one or more of a hollow tube, a solid wire, a flat sheet, a rough sheet, a water-in-oil emulsion, and a hollow grid; The surface of the growth substrate has a specific structure or is made of multiple materials; the specific structure includes a topological micron column, a cone array, a microfluidic channel or a porous grid; The various materials include glass, iron, copper, aluminum oxide, polydimethylsiloxane, polyethylene, polyimide or cross-linked polyurethane.

9. The method for preparing a multi-dimensional polymer nanostructure with controllable morphology according to claim 1, characterized in that: The external stimulation includes physical methods such as heat, magnetism, electricity, and light, and the duration of the external stimulation is 0-24 hours; Wherein, the thermophysical method includes thermal stimulation, which is used to adjust the growth environment temperature between 0-80°C; The magnetic physics method includes applying a magnetic field, and the magnetic field includes a parallel magnetic field and a uniform magnetic field, and the magnetic field intensity ranges from 0 to 50 mT, and the uniform magnetic field frequency ranges from 0 to 200 Hz; The electrophysical method includes electrical stimulation, and the electrical stimulation includes applying a voltage of a certain intensity, and the electrical stimulation power range is 0-36W; The photophysical method includes light stimulation, and the light stimulation includes applying light waves of a certain wavelength band, and the wavelength of the light waves is 450nm, 532nm, 808nm, and 1064nm.

10. The method for preparing a multi-dimensional polymer nanostructure with controllable morphology according to claim 1, characterized in that: The morphology of the nanostructure includes one or more combinations of a nano-burr structure, a nano-dot structure, a nano-wire structure, a nano-hole structure, and a nano-grid structure.

Citation Information

Patent Citations

  • Guide assembling method for nanometer structure

    CN104370274A

  • Vertically-oriented self-assembled segmented copolymer film, and production method and application thereof

    CN104829854A

  • Method for manufacturing nano-particle array of monodispersity having tunable size, nano-particle array manufactured by the same and the application thereof

    KR1020120123183A

  • Nanoparticles and fabrication thereof

    US20100137523A1